COP-27: A great opportunity to address the double crisis of food security and climate change–and for the EU to re-align its farm to fork strategy - Aerni, Philipp (Frontiers in Environmental Economics, 2023)
In the run-up to the conference on climate change in Sharm-el-Sheik, Egypt (https://cop27.eg/#/), many stakeholders called for a focus on the need to promote sustainable intensification in agriculture in order to render the world more food secure while striving toward a low carbon economy. In this context, European agricultural, environment and development policies have been challenged by several studies for not addressing the global challenges in an effective way. Especially the focus on agricultural extensification of the EU’s new farm-to-fork strategy as well as its current regulation of agricultural biotechnology are widely expected to lead to in food and feed imports from elsewhere – potentially leading to the offshoring of its environmental footprint. Moreover, the EU’s goal to export the f2f strategy via aid and trade incentives to low income countries where poverty rather than affluence is the main enemy of sustainability, may not be in line with commitment of European donors to respect the ownership principle in development cooperation. The internal review process of the EU suggests that adjustments in the implementation of the f2f strategy as well as a more responsive regulatory framework for the approval of crops developed with New Breeding Techniques (NBT) may help the EU to become more effective in addressing EU-wide as well as global sustainability challenges. It would enable European agriculture to become more sustainable, inclusive and productive while enabling food insecure African countries to better cope with the doubly challenge of food security and climate change.